Advertisement Remove all ads

Show That: 3 √ − 125 − 1000 = 3 √ − 125 × 3 √ − 1000 - Mathematics

Sum

Show that:\[\sqrt[3]{- 125 - 1000} = \sqrt[3]{- 125} \times \sqrt[3]{- 1000}\]

Advertisement Remove all ads

Solution

LHS = \[\sqrt[3]{- 125 \times - 1000} = \sqrt[3]{- 5 \times - 5 \times - 5 \times - 10 \times - 10 \times - 10} = \sqrt[3]{\left\{ - 5 \times - 5 \times - 5 \right\} \times \left\{ - 10 \times - 10 \times - 10 \right\}} = - 5 \times - 10 = 50\]

RHS =  \[\sqrt[3]{- 125} \times \sqrt[3]{- 1000} = \sqrt[3]{- 5 \times - 5 \times - 5} \times \sqrt[3]{\left\{ - 10 \times - 10 \times - 10 \right\}} = - 5 \times - 10 = 50\]

Because LHS is equal to RHS, the equation is true.

 
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Class 8 Maths
Chapter 4 Cubes and Cube Roots
Exercise 4.4 | Q 2.4 | Page 30
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×